PENINGKATAN KREATIVITAS PESERTA DIDIK DALAM PEMBELAJARAN SENI RUPA MELALUI PENDEKATAN TARL (TEACHING AT THE RIGHT LEVEL) KELAS X.3 SMAN 9 MAKASSAR - Nurhaida, Nurhaida (Nuansa Journal of Arts and Design, 2025)
ABSTRACTNurhaida, 2024. This research was motivated by the low level of student creativity in learning fine arts in the classroom. Many students feel they have no interest or talent in this field, so they tend to be passive during the learning process. Therefore, this research aims to increase students' creativity in arts and culture learning, especially in fine arts learning through the application of creative learning to class X.3 students at SMAN 9 Makassar. This research is Classroom Action Research (PTK) which involves a series of activities including planning, implementation, reflection and follow-up. Research data will be obtained through filling out questionnaires by students and direct observation of the learning process. The research results show a significant increase in student involvement in fine arts learning after implementing the creative learning model. The percentage of student involvement increased from 26% in pre-cycle to 66% in cycle I and reached 86% in cycle II. These findings confirm that implementing a learning model using the TaRL approach can be an effective strategy for increasing students' creativity in the fine arts learning process.